A Comprehensive Platform for Entrepreneurs Startup Guidance and Networking - Jebaraj, Bharath Singh; Sai, Devarapalli Hemanth; Kumar Reddy, N. Dileep; Kumar Reddy, Bhuma Manoj; Prudhvi, Chennareddy Venkata; K, Yalavarthi Vikas (2024 4th International Conference on Ubiquitous Computing and Intelligent Information Systems (ICUIS), 2024)
Entrepreneurial ecosystems are essential for fostering innovation, yet many entrepreneurs face barriers in accessing mentorship, networking, and resources critical for success. A comprehensive platform has been developed to support entrepreneurs by providing a unified space for networking, guidance, and collaboration. Key features include an idea-sharing page for peer and mentor feedback, an events calendar for workshops and webinars, and a community networking module that suggests relevant connections based on user interests. Real-time notifications ensure users stay informed about important updates, while a scalable infrastructure built on React.js, Node.js, and MongoDB supports seamless interactions. By bridging the gap between entrepreneurs, investors, and mentors, the platform enhances the entrepreneurial journey, enabling founders to connect, learn, and grow effectively. Evaluation results indicate high user engagement, active participation in idea sharing and events, and increased community involvement, highlighting the platform's role in fostering a dynamic and supportive entrepreneurial ecosystem.